Phenotypic traits of Mexican soybean seeds and their correlation with in vitro shoot induction and susceptibility to Agrobacterium infection - Mora Vásquez, Soledad; García-Lara, Silverio; Cardineau, Guy A. (Instituto de Ecología, A.C., 2018)
Background and Aims: Soybean regeneration and transformation are considered highly genotype-specific; however, little is known about desirable seed traits that could be useful indicators of their regeneration and transformation capacities. In the present study, eight commercially available Mexican soybean varieties, as well as the Jack genotype as a control, were phenotypically characterized to determine the seed traits that are important factors for their in vitro performance and susceptibility to Agrobacterium tumefaciens infection.Methods: Grain dimensions, seed weight, moisture, oil, protein, ash, carbohydrate content and macro and micro elements (Mg, K, Ca, P, Na, Mn, Fe, Cu and Zn) were measured and correlated with the corresponding direct shoot organogenesis capability and Agrobacterium infection susceptibility using the cotyledonary node as explant.Key results: Notably, the ash content was the only important factor that inversely correlated with the capacity for shoot organogenesis, whereas carbohydrate and phosphorus content were positively correlated with susceptibility to Agrobacterium infection. The best response in terms of multiple shoot formation and Agrobacterium transient transformation was observed with the soybean varieties Huasteca-100, Nainari and Suaqui-86, which have lower ash content and a higher carbohydrate and phosphorus content.Conclusions: In most reported studies, seed phenotypic traits have been overlooked as factors that influence their regeneration and transformation potential. In the present study, we present evidence of associations between some specific seed traits and regeneration and transient transformation of soybean.